COVID-19 in Costa Rica: longitudinal analysis of the transmission and death rates from the social inequality approach - García Marín, Anthony; García Fernández, Raúl (Población y Salud en Mesoamérica, 2022)
Introduction: this article addresses the relationship between the gross rates of transmission and the net death rates from COVID-19 -study variables-, with socioeconomic and health indicators -contrast variables- at four moments of observation during the first year of the syndemic in Costa Rica. The objectives of the research work are: a) identify the moments of observation based on the number of accumulated cases per epidemiological week; b) establish the statistical correlation between the crude rates of transmission and the contrast variables; c) establish the statistical correlation between the net death rates and the contrast variables; d) describe the development of transmission and death rates at the cantonal level, and e) socioeconomically characterize the cantons with very high values in those rates. Methodology: a study with a quantitative approach is developed through the statistical method and the application of hypothesis tests at a bivariate level, namely, Pearson and Spearman correlations. Results: the main results indicate that transmission is closely related, mostly, to socioeconomic factors -population density; Social Development Index (IDS); Human Development Index (HDI) and crime rates against property-, while deaths they are related to biological factors such as the rates of diseases -hypertension and respiratory-. Conclusions: the study demonstrates the relationship between disease and social inequalities, that is, how social inequality is reproduced in the field of health.